(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: This article focuses on the Parental Alienation Law – PAL (Law No. 12,318/2010), based on the theory of American psychiatrist Richard Gardner, evaluating its scientific weaknesses and the criticisms regarding the reinforcement of gender inequalities. Objectives: The study aims to assess the limitations of the Parental Alienation Law, question its punitive application, and discuss the impacts of this legislation on the protection of women and children, especially in the context of domestic violence reports. Methods: This is a descriptive qualitative research based on a literature review. Academic publications indexed in databases from 2014 to 2024 were analyzed, allowing an understanding of contemporary discussions on the topic. Results: The findings indicate that, despite the protective character of the legislation, it can be used as an instrument of institutional violence within the Justice System, perpetuating gender stereotypes and neglecting the complexities of family dynamics. Furthermore, the application of the law has delegitimized reports of domestic violence, compromising the comprehensive protection of victims. The role of social workers is highlighted as essential for critical analyses that incorporate power and gender relations in family disputes. Conclusion: It is concluded that the revocation of the Parental Alienation Law (Law No. 12,318/2010) is necessary, considering its impacts on the perpetuation of violence and inequalities. It is recommended to adopt public policies that promote the comprehensive protection of families, prioritize the prevention and confrontation of domestic violence, and ensure the fundamental rights of women and children.